Letters, Memory, Language: about Russian Transcultural Literature - Eleonora F. Shafranskaya (Polylinguality and Transcultural Practices, 2023)
The author of the article focuses on the image of letters as a symbol of national historical memory — on the example of Sukhbat Aflatuni’s story “Clay letters, floating apples”, where the letters act not only in their direct meaning, they are the antithesis of the imposed culture, language, historical interpretations. The article substantiates the legitimacy of using the term “transcultural literature” instead of the common and illogical one — “Russian-language literature”, since in this type of creativity the image of a different ethnic picture of the world, other national images of the world is paramount. The novel “Hands-rivers” by the contemporary writer Liana Shahverdyan is analyzed precisely in the categories of transcultural literature: the novel highlights the key themes and problems associated with the restoration of ancestral memory of family and the Armenian people, who, like millions of Soviet citizens, were subjected to Stalinist repressions. The metaphor of the carpet weaving culture, the carpet, the images of the local fauna — birds and snakes became the key ones in the analysis of the plot of the novel “Hands-rivers”. The novel by Liana Shahverdyan, based on archival documents, fills in the lost page of the history of the ХХth century, thus fitting into the current archival vector of the contemporary literary process.